Acriflavine modulates angiogenesis and tumor progression in ovarian cancer - España de Marco, Maria Jose (2023)
Ovarian cancer is one of the most lethal gynaecological malignancies. The development of new therapies is needed, as the five-year survival rate is less than 50%. Hypoxia is a feature of solid tumors associated with an aggressive phenotype. The main transcriptional factor involved in this process is Hypoxia Inducible Factor 1 alpha (HIF1α).